2014
DOI: 10.1097/brs.0000000000000289
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Missed Dynamic Canal Stenosis in the Cervical Spine

Abstract: Dynamic cord compression was most common at the C5-C6 segment. Cervical segments with greater disc bulge, more severe disc degeneration, greater angular motion, segmental kyphosis, and developmental stenosis may be at risk for missed dynamic stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 16 publications
2
34
0
1
Order By: Relevance
“…Our findings are consistent with what has been observed in humans. In a study of humans that evaluated kMRI in patients with cervical myelopathy, extension identified new spinal cord compressions most commonly at C5‐C6, followed by C4‐C5 . In a study that evaluated kMRI in human patients with cervical pain, extension caused the number of cervical disc protrusions to increase by 16.4% ,.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our findings are consistent with what has been observed in humans. In a study of humans that evaluated kMRI in patients with cervical myelopathy, extension identified new spinal cord compressions most commonly at C5‐C6, followed by C4‐C5 . In a study that evaluated kMRI in human patients with cervical pain, extension caused the number of cervical disc protrusions to increase by 16.4% ,.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, flexion has been shown to identify new compressive lesions that were not apparent in neutral position. In 1 study of human patients, the number of compressive lesions identified at C5‐C6 increased by 3.7% with flexion …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations